1995
DOI: 10.1200/jco.1995.13.6.1328
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic rescue after high-dose chemotherapy using autologous peripheral-blood progenitor cells or bone marrow: a randomized comparison.

Abstract: We conclude that the use of PBPC mobilized by chemotherapy plus G-CSF results in sustained trilineage reconstitution after HDCT, which occurs more rapidly as compared with BM. The earlier hematologic reconstitution in patients with PBPC rescue significantly reduces the time to transfusion independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
132
1
10

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(143 citation statements)
references
References 30 publications
0
132
1
10
Order By: Relevance
“…34,56,57 The target dose of infused CD34 þ cells varies from a minimum of 2.0 Â 10 6 CD34 þ cells/kg 31,58,59 to an optimal level of 5.0 Â 10 6 CD34 þ cells/kg. 24,26,55 Within this range, higher doses of infused CD34 þ cells are more beneficial for patients with MM and NHL.…”
Section: Mobilization Agent Mechanismmentioning
confidence: 99%
“…34,56,57 The target dose of infused CD34 þ cells varies from a minimum of 2.0 Â 10 6 CD34 þ cells/kg 31,58,59 to an optimal level of 5.0 Â 10 6 CD34 þ cells/kg. 24,26,55 Within this range, higher doses of infused CD34 þ cells are more beneficial for patients with MM and NHL.…”
Section: Mobilization Agent Mechanismmentioning
confidence: 99%
“…Seven patients recovered hematopoiesis timely in a median of 12 days for ANC Ͼ0.5 ϫ 10 3 / l and 14 days for platelets Ͼ20 ϫ 10 3 / l, time-periods which have been reported in patients with solid tumors and hematologic diseases following HDCT and PBPC rescue. 15,16 One patient, however, exhibited delayed ANC recovery on day +37 and failed to recover platelets until hospital discharge on day +55. The day of platelet recovery could not be determined exactly, because the patient reached platelet numbers Ͼ20 ϫ 10 3 / l after hospital release.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized study it has been shown that patients with germ cell cancer, who underwent HDCT with subsequent PBPC reinfusion, recovered hematopoiesis significantly faster than patients rescued by bone marrow. 15 Therefore, the present study focused on the feasibility of mobilization and collection of PBPC in pretreated patients with metastatic STS. Mobilization of PBPC is usually performed by cyclophosphamide and/or growth factor in various malignant diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations